The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/plants11091184
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Mediated Knockout of the OsbHLH024 Transcription Factor Improves Salt Stress Resistance in Rice (Oryza sativa L.)

Abstract: Salinity stress is one of the most prominent abiotic stresses that negatively affect crop production. Transcription factors (TFs) are involved in the absorption, transport, or compartmentation of sodium (Na+) or potassium (K+) to resist salt stress. The basic helix–loop–helix (bHLH) is a TF gene family critical for plant growth and stress responses, including salinity. Herein, we used the CRISPR/Cas9 strategy to generate the gene editing mutant to investigate the role of OsbHLH024 in rice under salt stress. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…The most effective way to break yield barriers is through hybridization. It's not a good idea to choose parents based on their phenotypic performance alone, because lines with good phenotypes may produce bad recombinants in the generations that follow [ 18 ]. So, it is important that parents are chosen based on how well they can work together.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective way to break yield barriers is through hybridization. It's not a good idea to choose parents based on their phenotypic performance alone, because lines with good phenotypes may produce bad recombinants in the generations that follow [ 18 ]. So, it is important that parents are chosen based on how well they can work together.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that drought-tolerant inbred lines can be identified using physiological traits as evidence from PCA. There are numerous studies that support these findings ( Negrão et al, 2017 ; Zhao et al, 2019 ; Maqbool et al, 2020 ; Zhu et al, 2021 ; Alam et al, 2022 ).…”
Section: Discussionmentioning
confidence: 85%
“…Earlier reports confirmed that the antimicrobial activity of AgNPs was different depending on microbial species (Ouda, 2014). AgNPs can significantly delay mycelial growth in a dose-dependent manner in vitro (Aguilar-Méndez et al, 2011;Alam et al, 2022). AgNPs may directly attach to and penetrate the cell membrane to kill spores, while the penetration of AgNPs into microbial cell membranes is not clearly understood (Hwang et al, 2008).…”
Section: Discussionmentioning
confidence: 95%